Fake COVID-19 vaccines: scams hampering the vaccination drive in India and possibly other countries - Om Prakash Choudhary; Priyanka; Indraj Singh; Teroj A. Mohammed; Alfonso J. Rodriguez-Morales (Taylor & Francis Group, 2021)
India is executing a mass vaccination program to restrict the predicted third wave of COVID-19. However, fake COVID-19 vaccines have emerged as a major challenge amid the vaccination drive in India. This article highlights the loopholes and measures to restrict the fake COVID-19 vaccination scams. Such activities have put the genuinity of vaccination certificates under scanner besides putting public health at risk and instigating vaccine hesitancy. Hence, the Government of India needs to take stringent actions such as complete take-over of COVID-19 vaccine procurement and free immunization. Furthermore, the public needs to remain vigilant and check vaccination certificates immediately after being vaccinated. Such efforts on the part of the government and public can completely restrict fake vaccinations.